Multimodal magnetic resonance neuroimaging measures characteristic of early cART‐treated pediatric HIV: A feature selection approach. Issue 13 (16th May 2022) - Khobo, Isaac L.; Jankiewicz, Marcin; Holmes, Martha J.; Little, Francesca; Cotton, Mark F.; Laughton, Barbara; van der Kouwe, Andre J. W.; Moreau, Allison; Nwosu, Emmanuel; Meintjes, Ernesta M.; Robertson, Frances C.
Abstract: Children with perinatally acquired HIV (CPHIV) have poor cognitive outcomes despite early combination antiretroviral therapy (cART). While CPHIV‐related brain alterations can be investigated separately using proton magnetic resonance spectroscopy ( 1 H‐MRS), structural magnetic resonance imaging (sMRI), diffusion tensor imaging (DTI), and functional MRI (fMRI), a set of multimodal MRI measures characteristic of children on cART has not been previously identified. We used the embedded feature selection of a logistic elastic‐net (EN) regularization to select neuroimaging measures that distinguish CPHIV from controls and measured their classification performance via the area under the receiver operating characteristic curve (AUC) using repeated cross validation. We also wished to establish whether combining MRI modalities improved the models. In single modality analysis, sMRI volumes performed best followed by DTI, whereas individual EN models on spectroscopic, gyrification, and cortical thickness measures showed no class discrimination capability. Adding DTI and 1 H‐MRS in basal measures to sMRI volumes produced the highest classification performance validation accuracy = 85 % AUC = 0.80 . The best multimodal MRI set consisted of 22 DTI and sMRI volume features, which included reduced volumes of the bilateral globus pallidus and amygdala, as well as increased mean diffusivity (MD) and radial diffusivity (RD) in the right corticospinal tract in cART‐treated CPHIV. Consistent with previous studies of CPHIV, select subcortical volumes obtained from sMRI provide reasonable discrimination between CPHIV and controls. This may give insight into neuroimaging measures that are relevant in understanding the effects of HIV on the brain, thereby providing a starting point for evaluating their link with cognitive performance in CPHIV. Abstract : This multimodal MRI study aims to identify a pattern of neuroimaging measures characteristic of pediatric HIV by using supervised learning and embedded feature selection. Our findings support previously reported literature on the ongoing neurological effects that HIV has on subcortical volumes and white matter integrity.